A patologia esquizoide: um estudo a partir das contribuições de D. W. Winnicott - Veronica, Luiz Fernando Rodrigues (2018)
The aim of this study was to present the contributions of D. W. Winnicott on schizoid pathology, seeking to explain the place that this pathology occupies in the theoretical and clinical framework of the author and also the aspects related to etiology, dynamics and clinical management highlighted by the author. This is a theoretical research, where the results were based on a detailed reading of the author’s work and two of his clinical cases, diagnosed by him as schizoid. It had as a methodological basis the principle of hermeneutics, which considers the articulation of the whole with the parts, understanding the meaning as relative to the context, so that the whole is understood in relation to its parts and the parts in relation to the whole. As results, the author locates schizoidia in the field of psychoses, having its origin in the earliest period of life, before the individual has achieved a more consistent integration of the self. Schizoid individuals suffered abrupt, disastrous failures as a result of a chaotic environment, they still succeeded in forming, even in a very incipient way, a self. The consequence of environmental failures in schizoids, produces a near-permanent sensation that the world and everything relating to the external or shared reality is dangerous and pernicious. Therefore, their attitude is to always flee from the world, from contact, from relationships, living circumscribed to their subjective world, in order to protect their incipient self, against the unpredictability and invasion of the environment